DOMESTIC VIOLENCE AGAINST MEN IN ACEH: AN ANALYSIS OF CAUSES AND IMPACTS - Saputra, Hijrah; Amalia, Wirda; Rusnawati, Rusnawati; Husen Ismail, Faisal Bin (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Domestic violence is a topic that is frequently debated and discussed, even widely reported on social media, where most husbands or men are portrayed as perpetrators of domestic violence and wives as the victims. However, it is known that within the household, anyone has a significant potential to become a perpetrator. Men as victims of domestic violence are often overlooked in social and legal discourses. This study aims to analyze the causes and impacts of domestic violence against men. The research methodology used is a qualitative approach with data collection techniques including observation, documentation, and interviews. This research was conducted in Aceh Besar District and Banda Aceh City. The study found that power dynamics in relationships, economic imbalance, and rigid gender roles contribute to the worsening condition of male victims. The impacts experienced by men who are subjected to domestic violence tend to include feelings of shame, stigma, and difficulty in accessing help due to social constructs that expect men to be strong and not show weakness. This study provides insight into the need for greater attention to men as victims of domestic violence and emphasizes the importance of changing societal perspectives and policies to create a more inclusive and responsive system for victims of all genders.